Detection of Borrelia DNA in Ornithodoros tholozani ticks and their eggs - Afsaneh Aghaei; Behnaz Ghazinezhad; Saied Reza Naddaf (Pasteur Institute of Iran, 2014)
Introduction: Spirochetes of Borrelia can be visualized directly in infected ticks by dark-field microscopy. Inoculation of in phosphate buffered saline (PBS) suspension of ground Argasid soft ticks to susceptible animals or allowing the ticks to feed on the same species followed by microscopic examination of the animals' blood have also been practiced. With the advent of molecular methods and introduction of various gene markers, Borrelia persica DNA was detected in Ornithodoros tholozani ticks by using several gene markers, but the data on transovarial transmission of Borrelia in this tick by these methods is very scarce. Methods: In this study we tried to detect Borrelia in field collected O. tholozani ticks by allowing them to feed on guinea pigs and then to examine the animals' blood for spirochetes by microscopy. We also used two PCR methods targeting highly repetitive regions of rrs gene to detect Borrelia DNA in adult ticks, larvae, and eggs. Results: All the guinea pig blood samples were negative for spirochetes by microscopy. However, out of the 17 adult ticks, 2 males and 5 females were positive for Borrelia DNA.  None of the larvae was positive, but two batches of eggs yielded the expected 540 bp amplicon by nested PCR. Conclusion: Presence of Borrelia DNA in adult O. tholozani ticks and their eggs is an indication for transovarial transmission of relapsing fever agent in this tick.